The "Triplex Confinium" in Habsburg-Venetian Relations at the End of the Seventeenth Century - Holjevac, Željko (Array, 2000)
On the basis of extensive archival research in Graz, the author attempts to present the new border realities as reflected in relations between the Imperial powers and the regions of both Lika and krbava and the northern Adriatic. Particular attention is given to the interdependencies of several processes and activities constituting the new realities on the border, like the salt trade (including smuggling, etc.), misunderstandings regarding the borderlines, suspicions regarding the intentions of the "other", etc. All these turned to be problems which determined the complex nature of the "Triplex Confinium" even before it was constituted in legal terms.